Avaliação de parâmetros hematológicos e comportamentais de diferentes técnicas de coleta de sangue venoso de felinos - Veleda, Patrícia Alvez (2018)
Exams laboratory have as function main auxiliary in the diagnosis, together with the physical exam and the patient's clinical history. In that context, it is indispensable that the collection of blood is accomplished in a correct way for not interfering in their results. The puncturing the jugular vein is the technique more used in the clinical routine for the collection of blood in felines. However, for most of the felines, that technique is uncomfortable and stressful. The main consequence resulting from the stress during the collection of blood, in that species, is the appearance of alterations of hematological parameters, as the platelet aggregation, that a lot of times make unfeasible the analysis needs the exam. So, a technique used in human pediatrics was adapted for the collection blood in felines, with the objective of minimizing the stress and, like this, to prevent the formation of attachés platelet during the sampling of blood. For that, they were selected, for collection of sanguine samples, 110 felines healthy of any sex, race, age and weight. The animals were distributed randomly in two groups, being them GCJ (group jugular collection) and GCG (group collects dripping), both with 55 animals. It was collected 2ml of blood, or by puncture of the right jugular vein with syringe of 3ml and needle 25x8 in the group GCJ or by insert of outlying veined catheter 22G in the right cephalic vein in the group GCG. The volume of 0,5mL of blood was conditioned in tube containing ethylenediaminetetraacetic acid (EDTA) and 1,5ml in tubes without anticoagulants. The analyzed parameters were complete blood count, blood glucose, bruise formation in the place of the puncture, occurrence of aggregation platelet and stress score. The results showed that the platelet aggregation and the stress score were smaller statistically in GCG. The technique of collection of blood by dripping of the cephalic vein of felines was shown more appropriate for the feline species for to minimize the stress behavioral and to reduce the occurrence of platelet aggregation without altering the other hematological parameters.